Вы находитесь на странице: 1из 18

FROM ABOVE TQO EQUATIONS

M(x ) = - Q( x )

M ( x ) = CONSTANT. = M0 .

D1= ( EI )e

USING EQ (3-28/P32 )

D1=linalg[matrix](4,1,[E*I1,2*E*I1,2.*E*I1,E*I1]);Q1=linalg
[matrix](4,1,[-M0,-M0,-M0,-
M0]);L1=linalg[matrix](4,1,[H/4.,H/4.,H/4.,H/4.]);

1
for i from 1 by 1 to 4 do
S[i]=D1[i,1]/L1[i,1];S1[i]=Q1[i,1]*L1[i,1]/2.;

end do;

2
D_BY_L=matrix(4,1,[S[1],S[2],S[3],S[4]]);QL_BY_2=matrix(4,1
,[S1[1],S1[2],S1[3],S1[4]]);

for i from 2 by 1 to 4 do
R[i,1]=-D_BY_L[i-1,1]*PHI[i-1,1]+(D_BY_L[i-
1,1]+D_BY_L[i,1])*PHI[i,1]-D_BY_L[i,1]*PHI[i+1,1]-
QL_BY_2[i-1,1]-1.0*QL_BY_2[i,1];

3
end do;

PHI[1,1]=0.;PHI[5,1]=0.;E2=R[2,1];E3=R[3,1];E4=R[4,1];

G=solve({E2, E3,E4}, {PHI[2,1],PHI[3,1],PHI[4,1]});


assign(G);PHI[2,1];PHI[3,1],PHI[4,1];

4
PHIN[2,1]=simplify(PHI[2,1]);PHIN[3,1]=simplify(PHI[3,1]);P
HIN[4,1]=simplify(PHI[4,1]);

PROBLEM 3- 2

5
PROBLEM 3-1 PART ( b )

In this problem , the deflection Y at x= (3/16) H is to be found out.

We have already calculated as :

> Y1:=0.0; Y2:=-.9375000000e-1/E/I1*M0*H^2;


Y1 := 0.
0.09375000000 M0 H 2
Y2 :=
E I1
Nj at NODE 2 will be equal to 1 at the element length H/4.

Therefore, Nj at x= 3.*H/16. will be

> Nj_x:=(3.*H/16.)/(H/4.);
Nj_x := 0.7500000000
> Ni_x:=1.0-Nj_x;
Ni_x := 0.2500000000
> Y_x:=(Ni_x)*Y1+(Nj_x)*Y2;
0.07031250000 M0 H 2
Y_x :=
E I1
> E1:=D1*diff(PHI(x),x$2) +Q(x)=0;E2:=q(x)=-
D1*diff(PHI(x),x);

Q ( x ) = 0 NO HEAT GENERATED TERM

Q IS SAME AS Q1 BELOW.

USING EQ. ( 3-28 /P32 ) :

D1 = linalg[matrix](3,1,[0.02,0.005,0.0035]);Q1 =
linalg[matrix](3,1,[0.,0.,0.]);L1 =
linalg[matrix](3,1,[1.3,8.,2.5]);

6
D1[1,1];

for i from 1 by 1 to 3 do
S[i] = D1[i,1]/L1[i,1];S1[i] = Q1[i,1]*L1[i,1]/2.;

end do;

D_BY_L = matrix(3,1,[S[1],S[2],S[3]]);QL_BY_2 =
matrix(3,1,[S1[1],S1[2],S1[3]]);

7
for i from 2 by 1 to 3 do
R[i,1] = -D_BY_L[i-1,1]*PHI[i-1,1]+(D_BY_L[i-
1,1]+D_BY_L[i,1])*PHI[i,1]-D_BY_L[i,1]*PHI[i+1,1]-
QL_BY_2[i-1,1]-1.0*QL_BY_2[i,1];
end do;

GIVEN BOUNDARY CONDITIONS


PHI[1,1] = 20.;PHI[4,1] = -15.;E2 = R[2,1];E3 = R[3,1];

G = solve({E2, E3}, {PHI[2,1],PHI[3,1]});


assign(G);PHI[2,1];PHI[3,1];

8
q[1] = -D1[1,1]*((PHI[2,1]-PHI[1,1])/L1[1,1]);

q[2] = -D1[2,1]*((PHI[3,1]-PHI[2,1])/L1[2,1]);

q[3] = -D1[3,1]*((PHI[4,1]-PHI[3,1])/L1[3,1]);

9
PROBLEM 3-5

10
THE EQ. ( 3.12 ) is for the INTERIOR NODES

The problem here is to derive the equation for the FIRST NODE.

The derivation is as follows:

PROBLEM 3-5

11
PROBLEM 3- 8

14
PROBLEM 3-8

FROM EQS( 1) AND 2, ONE GETS

D1= E*I =2*10^10 ;


Q(x) = - M( x ) . VALUES FROM FIG ABOVE.
L1 = VALUES FROM FIG ABOVE.

PLEASE NOTE :

( D1/L )e CONSTANT ACROSS THE ELEMENTS

D1=linalg[matrix](4,1,[2.0*10^10,2.0*10^10,2.0*10^10,2.0*10
^10]);Q1 =linalg[matrix](5,1,[0.,-2.*10^6,-4.*10^6,-
2.*10^6,0.]);L1 =linalg[matrix](4,1,[200.,200.,200.,200.]);

15
for i from 1 by 1 to 4 do
S[i] =D1[i,1]/L1[i,1];

end do;

D_BY_L =matrix(4,1,[S[1],S[2],S[3],S[4]]);

EQUATION 3-28 MODIFIED DUE TO CONSTANT ( D/L ) OR D

16
for i from 2 by 1 to 4 do
R[i,1] =D_BY_L[i-1,1]*(-PHI[i-1,1]+2.*PHI[i,1]-
PHI[i+1,1])-(L1[i,1]/6)*(Q1[i-1,1]+4.*Q1[i,1]+Q1[i+1,1]);

end do;

BOUNDARY CONDITIONS:

PHI[1,1] =0.;PHI[5,1] =0.;E2 =R[2,1];E3 =R[3,1];E4


=R[4,1];

G =solve({E2, E3,E4}, {PHI[2,1],PHI[3,1],PHI[4,1]});


assign(G);PHI[2,1];PHI[3,1],PHI[4,1];

17
18